One way to the top: How services boost the demand for goods - Andrea Ariu; Florian Mayneris; Mathieu Parenti (National Bank of Belgium, 2018)
In this paper, we take advantage of a uniquely detailed dataset on firm-level exports of both goods and services to show that demand complementarities between services and goods enable firms to boost their manufacturing exports by also providing services. The positive causal effect of services accounts for up to 25% of the manufacturing exports of bi-exporters (i.e. the firms that export both goods and services), and 12% of overall goods exports from Belgium. We find that by associating services with their goods, bi-exporters increase both the quantities and the prices of their goods. To rationalize these findings, we develop a new model of oligopolistic competition featuring one-way complementarity between goods and services, product differentiation, and love for variety. By supplying services with their goods, firms increase their market share, and hence their market power and markup. The model then shows that exporting services acts as a demand shifter for firms, increasing the perceived quality of their products. Going back to the data, we find strong confirmation for this mechanism.
Keywords: F10; F14; L80; 330; Demand complementarities; Goods & services; Firm-level exports; Quality